Light microscopy with differential staining techniques for the characterisation and discrimination of insects versus marine arthropods processed animal proteins. Issue 8 (3rd August 2017) - Ottoboni, Matteo; Tretola, Marco; Cheli, Federica; Marchis, Daniela; Veys, Pascal; Baeten, Vincent; Pinotti, Luciano
ABSTRACT: The aim of this study was to evaluate the use of light microscopy with differential staining techniques for the discrimination of insect material from marine arthropods – classified as fishmeal. Specifically, three samples of single-species insect material, Hermetia illucens (HI), Bombyx mori (BM) and Tenebrio molitor (TM), and two samples of marine arthropods, shrimp material and krill, were analysed and compared after staining by two reagents to enhance fragment identification. Alizarin Red (AR) and Chlorazol Black (CB), which react respectively with calcium salts and chitin, were tested for their potential efficacy in distinguishing between insect and marine materials. Results indicated that AR failed to stain HI, BM and TM materials. By contrast, the three insect species materials tested were stained by CB. When shrimp fragments and krill were considered, AR and CB stained marine materials reddish-pink and light blue to black, respectively. By combining these results, it can be suggested that CB staining may efficiently be used to mark insect materials; AR does stain shrimp fragments but does not stain the tested insect material, indicating a possible approach for discriminating between insects and marine arthropods. However, since the present study was performed on pure materials and a small set of samples, possible implementation of this technique still needs to be confirmed in complex matrices such as compound feed.